An external quality assessment feasibility study; cross laboratory comparison of haemagglutination inhibition assay and microneutralization assay performance for seasonal influenza serology testing: A FLUCOP study - Waldock, Joanna; Weiss, Carol D.; Wang, Wei; Levine, Min Z.; Jefferson, Stacie N.; Ho, Sammy; Hoschler, Katja; Londt, Brandon Z.; Masat, Elisa; Carolan, Louise; Sánchez-Ovando, Stephany; Fox, Annette; et al. (Frontiers in Immunology, 2023)
External Quality Assessment (EQA) schemes are designed to provide a snapshot of laboratory proficiency, identifying issues and providing feedback to improve laboratory performance and inter-laboratory agreement in testing. Currently there are no international EQA schemes for seasonal influenza serology testing. Here we present a feasibility study for conducting an EQA scheme for influenza serology methods. We invited participant laboratories from industry, contract research organisations (CROs), academia and public health institutions who regularly conduct haemagglutination inhibition (HAI) and microneutralisation (MN) assays and have an interest in serology standardisation. In total 16 laboratories returned data including 19 data sets for HAI assays and 9 data sets for MN assays. Within run analysis demonstrated good laboratory performance for HAI, with intrinsically higher levels of intra-assay variation for MN assays. Between run analysis showed laboratory and strain specific issues, particularly with B strains for HAI, whilst MN testing was consistently good across labs and strains. Inter-laboratory variability was higher for MN assays than HAI, however both assays showed a significant reduction in inter-laboratory variation when a human sera pool is used as a standard for normalisation. This study has received positive feedback from participants, highlighting the benefit such an EQA scheme would have on improving laboratory performance, reducing inter-laboratory variation and raising awareness of both harmonised protocol use and the benefit of biological standards for seasonal influenza serology testing.